Mengembangkan Konsep dan Pengukuran Pengasuhan dalam Perspektif Kontekstual Budaya - Agnes Indar Etikawati; Juke Roosjati Siregar; Hanna Widjaja; Ratna Jatnika (Buletin Psikologi, 2019)
Beliefs and goals in parenting are influenced by the expectations of society or local culture. Therefore, the measurement of parenting should be developed from a contextual perspective. The development of the measurement conducted inductively which started with the phase of indigenous concept exploration. The participants are parents living in a particular area, having a local ethnic identity, using local language and customs in their daily lives. The method of data collection is an interview or focus group discussion (FGD), with questions that refer to the parenting element according to Darling & Steinberg. Two alternative data analysis can be done; to obtain the construct at the level of parenting practice or construct at the level of parenting style. The construct then is developed into an instrument by following the scale development guidelines in which includes item writing, content validation, scale administration, and psychometric evaluation.